Zero Verdict against Perpetrators of Corruption in Decision Number 49/Pid.Sus.TPK/2021/PN.Jkt: An Analysis of Islamic Criminal Law Perspectives - Muhammad Wahyu Hidayat; Noor Azizah (Lambung Mangkurat Law Journal, 2025)
This study examines the basis of legal considerations behind the imposition of a null verdict against Benny Tjokrosaputro in the case of corruption of PT. Jiwasraya Insurance and PT. Asabri, which resulted in state losses of Rp40 trillion. The main focus of this research is an analysis of Decision Number 49/Pid.Sus.TPK/2021/PN.Jkt from the perspective of Islamic criminal law (jinayah), especially related to the compatibility between the null verdict and the principle of justice in Islamic law. This study aims to reveal the extent to which the verdict reflects the incompatibility between Indonesia's positive legal system and the values of justice and deterrence emphasized in Islamic criminal law. The research method used is normative juridical with a literature study approach, case study, and legal comparison between Indonesian positive law and Islamic criminal law. The analysis was carried out qualitatively on relevant legal documents and literature. The results of the study show that the zero verdict in the verdict is based on the consideration of the accumulated criminal sentence that was previously handed down in other cases. However, from the perspective of Islamic criminal law, a zero verdict has the potential to ignore the principles of substantive justice, proportionality of punishment, and the public interest, given the widespread impact of corruption on society and the state. This study concludes that there is a missynchronization between the principles of punishment in positive law and Islamic criminal law in handling major corruption cases. Therefore, it is suggested that further studies are needed to build harmonization between the two legal systems in order to realize more substantial and effective justice in eradicating corruption.